A concise guide to macroeconomics : what managers, executives, and students need to know - Moss, David A. (Boston : Harvard Business Review Press, 2014)
"Understanding the Ground Rules for the Global Economy In this revised and updated edition of A Concise Guide to Macroeconomics, David A. Moss draws on his years of teaching at Harvard Business School to explain important macro concepts using clear and engaging language. This guidebook covers the essentials of macroeconomics and examines, in a simple and intuitive way, the core ideas of output, money, and expectations. Early chapters leave you with an understanding of everything from fiscal policy and central banking to business cycles and international trade. Later chapters provide a brief monetary history of the United States as well as the basics of macroeconomic accounting. You'll learn why countries trade, why exchange rates move, and what makes an economy grow. Moss's detailed examples will arm you with a clear picture of how the economy works and how key variables impact business and will equip you to anticipate and respond to major macroeconomic events, such as a sudden depreciation of the real exchange rate or a steep hike in the federal funds rate. Read this book from start to finish for a complete overview of macroeconomics, or use it as a reference when you're confronted with specific challenges, like the need to make sense of monetary policy or to read a balance of payments statement. Either way, you'll come away with a broad understanding of the subject and its key pieces, and you'll be empowered to make smarter business decisions. "--
"Now more than ever before, executives and managers need to understand their larger economic context. In A Concise Guide to Macroeconomics, David Moss leverages his many years of teaching experience at Harvard Business School to lay out important macroeconomic concepts in engaging, clear, and concise terms. In a simple and intuitive way, he breaks down the ideas into output, money, and expectations. In addition, Moss introduces powerful tools for interpreting the big-picture economic developments that shape events in the contemporary business arena. He uses detailed examples drawn from history to illuminate important concepts, and leaves the reader with a clearer picture of how our abstract economy actually works, and what impact in has on business. This classic resource is fully updated, including a new chapter on the Global Financial Crisis"--
Keywords: Macroeconomics; Economic policy; Economic development; Monetary policy -- United States; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Economics / Macroeconomics; BUSINESS & ECONOMICS / Finance